A New Effort to Diversify Faculty: Postdoc-to-Tenure Track Conversion Models - Culpepper, Dawn; Reed, Autumn M.; Enekwe, Blessing; Carter-Veale, Wendy; LaCourse, William R.; McDermott, Patrice; Cresiski, Robin H. (Frontiers in Psychology, 2021)
Calls to diversify the professoriate have been ongoing for decades. However, despite increasing numbers of scholars from underrepresented racial minority groups earning doctorates, actual progress has been slow, particularly across STEM disciplines. In recent years, new efforts have emerged to recruit faculty members from underrepresented racial minority groups (i.e., African American/Black, Hispanic/Latinx, and/or Native American/Native Hawaiian/Indigenous) through highly competitive postdoctoral programs that allow fellows the opportunity to transition (or “convert”) into tenure-track roles. These programs hybridize some conventional aspects of the faculty search process (e.g., structured interview processes that facilitate unit buy-in) along with novel evidence-based practices and structural supports (e.g., proactive recruitment, cohort communities, search waivers, professional development, enhanced mentorship, financial incentives). In this policy and practice review, we describe and synthesize key attributes of existing conversion programs at institutional, consortium, and system levels. We discuss commonalities and unique features across models (N=38) and draw specific insights from postdoctoral conversion models developed within and across institutions in the University System of Maryland (USM). In particular, experience garnered from a 10-year-old postdoc conversion program at UMBC will be highlighted, as well as the development of an additional institutional model aimed at the life sciences a state-system model of faculty diversification with support from a NSF Alliances for Graduate Education and the Professoriate (AGEP) grant.